Burnout in Pediatric Nephrology Fellows and Faculty: Lessons From the Sustainable Pediatric Nephrology Workforce Project (SUPERPOWER) - Halbach, Susan M.; Pillutla, Kartik; Seo-Mayer, Patricia; Schwartz, Alan; Weidemann, Darcy; Mahan, John D. (Frontiers in Pediatrics, 2022)
Physician well-being is an important contributor to both job satisfaction and patient outcomes. Rates of burnout among physicians vary by specialty, ranging from 35-70%. Among pediatric residents, longitudinal data demonstrates consistent rates of burnout around 50-60%, although little is known about burnout among pediatric subspecialty fellows. Specifically, the degree of burnout among pediatric nephrologists remains unknown, as does the impact faculty burnout may have on trainee burnout. We sought to evaluate prevalence and predictors of burnout among US pediatric nephrology fellows and faculty, and assess for interactions between groups. In this multi-center pilot survey of all United States pediatric nephrology training programs from February – April 2020, burnout was assessed through abbreviated Maslach Burnout Inventory and predictors were explored through survey items devoted to demographic, personal characteristics, and job and career satisfaction questions. A total of 30/34 available fellows and 86/102 faculty from 11 institutions completed the survey (overall response rate 85%). The prevalence of burnout was 13% among fellows and 16% among faculty. Demographic (age, gender, year of training, faculty rank, marital status) and program factors (fellowship size, faculty size, current block/rotation, vacation or weekend off timing) were not significantly associated with burnout. Faculty and fellows with burnout reported significantly lower quality of life (5.3 vs 7.9, p<0.05), higher perceived stress (2.4 vs. 1.4, p<0.05) and lower satisfaction with career choice (66% vs. 22%) and work life balance (28% vs. 0%), compared to those without burnout (p<0.05 for all). Other important factors positively associated with burnout included lower institutional support for wellness programs and lower satisfaction with both colleague and faculty support. Larger studies are needed to explore if burnout is truly less prevalent among pediatric nephrology fellows and faculty compared to pediatric residents and graduate physicians. A larger sample size is also necessary to determine whether any interactions exist between the faculty and trainee roles in the developments of burnout. Future studies should also explore how to promote well-being through addressing key factors such as overall learning/working environment, stress reduction, and building personal resilience.